Risk Factors and Symptoms of Ovarian Cancer in Patients Attending Hiwa Oncology/Hematology Hospital in Sulaimaniyah City - Hadeel A. Ibrahim; Amani F. Abbas (Kufa Journal for Nursing Sciences)
Background: Ovarian cancer is responsible for higher mortality rate than any other cancer of the woman genital system.